2019
DOI: 10.1016/j.celrep.2019.04.100
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Block of Cerebellar Outflow Reveals Cortical Circuitry for Motor Coordination

Abstract: Highlights d High-frequency stimulation blocked cerebellar outflow and impaired motor behavior d Response patterns and coordinated firing of CTC neurons were disrupted d The spatial tuning and early preparatory activity of neurons were unaffected d Cerebellar control of local and global cortical synchrony supports motor timing

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(68 citation statements)
references
References 55 publications
7
54
0
Order By: Relevance
“…We previously posited that the excitation/inhibition interplay triggered by the CTC input plays a role in generating the firing transient at the onset of movement (Nashef et al, 2018a). Consistent with this hypothesis, blocking the cerebellar outflow by dentate cooling (Hore and Flament, 1988) or high frequency stimulation in the SCP (Nashef et al, 2019) abolishes this transient, particularly in cortical cells that integrate CTC input. The loss of this transient was accompanied by ataxic movements.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…We previously posited that the excitation/inhibition interplay triggered by the CTC input plays a role in generating the firing transient at the onset of movement (Nashef et al, 2018a). Consistent with this hypothesis, blocking the cerebellar outflow by dentate cooling (Hore and Flament, 1988) or high frequency stimulation in the SCP (Nashef et al, 2019) abolishes this transient, particularly in cortical cells that integrate CTC input. The loss of this transient was accompanied by ataxic movements.…”
Section: Discussionmentioning
confidence: 71%
“…We implanted stimulating electrodes in the SCP (Figure 1) of monkeys (n=3) that were trained to wear an exoskeleton (Kinarm system) and perform a center-out reaching task ( Figure 1A-B). The behavioral task used here was designed to encourage the monkeys to move as fast as possible by predicting the time of the "go" signal (Nashef et al, 2019). Neural activity was recorded from arm-related motor cortical areas using multiple single electrodes in 3 monkeys ( Figure 1C); in two of these animals, neurons were also tested using a 3-barrel recording pipette (Thiele et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the cerebellum receives information from the primary motor and premotor cortex through the pons. Recent studies have demonstrated that the cerebellarthalamo-cortical system plays an important role in motor control (Viaro et al, 2017;Nashef et al, 2018Nashef et al, , 2019 and motor learning (Tanaka et al, 2018). A recent study also demonstrated that the cortico-cerebellar loop contributes to cognitive processes (Gao et al, 2018).…”
Section: Toward Building a Whole-brain Network Modelmentioning
confidence: 99%